APPLICATION OF RESOURCE-SAVING TECHNOLOGIES FOR MANUFACTURING MACHINE PARTS (Intent Research Scientific Journal, 2023)
The article covers an analysis of optimization of the technological process (TP) in order to select technological solutions at various design levels and ensure the minimum value of the reduced costs while simultaneous observing a number of technical restrictions.